2018
DOI: 10.1177/0003319718790876
|View full text |Cite
|
Sign up to set email alerts
|

Greater Exercise Pressor Response Is Associated With Impaired Claudication Outcomes in Symptomatic Peripheral Artery Disease

Abstract: We determined whether a greater exercise pressor response during a constant-load treadmill test was associated with lower peak walking time (PWT) and claudication onset time (COT) measured during a graded maximal treadmill test in 304 patients with symptomatic peripheral artery disease (PAD). The exercise pressor response was assessed by measuring heart rate and blood pressure (BP) at rest and during a constant-load treadmill test (speed = 2 mph, grade = 0%). After only 2 minutes of walking, mean heart rate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Previously, we have shown that the exaggerated BP response to exercise is associated with worse functional outcomes such as shorter COT and PWT. 19 Findings from the current report support this association and extend our previous results by showing that the association between exaggerated exercise pressor response and shorter COT and PWT is not due to differences in comorbid burden.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previously, we have shown that the exaggerated BP response to exercise is associated with worse functional outcomes such as shorter COT and PWT. 19 Findings from the current report support this association and extend our previous results by showing that the association between exaggerated exercise pressor response and shorter COT and PWT is not due to differences in comorbid burden.…”
Section: Discussionsupporting
confidence: 90%
“…The changes in BP and HR values from rest to the completion of the first 2 minutes of exercise were calculated and used to quantify the exercise pressor response, as previously reported. 19 Determining the exercise pressor response after only 2 minutes of the treadmill test was done because walking for this duration at this work stage (2 mph speed, 0% incline) was more predictive of the clinically relevant outcomes of COT and PWT than when the exercise pressor response was determined at later exercise time points. 19…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing and composition of nutritional support, in particular supplementary protein, is critical in achieving optimal outcomes for exercise interventions [50,51]. Nutrients with anti-oxidant and anti-inflammatory properties are also essential, not only to treat the underlying atherosclerotic systemic disease state, but also in light of recent work in patients with IC demonstrating a negative association between walking performance and markers of endothelial cell inflammation and a positive association with ambulatory ability and circulating anti-oxidant capacity [52].…”
Section: Nutrition In the Management Of Peripheral Arterial Diseasementioning
confidence: 99%
“…15 Furthermore, we recently found that a greater exercise pressor response is independently associated with impaired treadmill claudication outcomes. 16 Finally, a greater exercise pressor response in patients with PAD indicates a greater increase in their blood pressure and heart rate at a given exercise intensity, 17 thereby increasing the work of the heart and possibly the risk of an adverse event during an exercise session, such as acute myocardial infarction or sudden cardiac death. 18 Based on the previous findings, there are a few possible mechanisms for an exaggerated exercise pressor response in PAD.…”
Section: Introductionmentioning
confidence: 99%